CATAMNESIS OF PATIENTS WITH INFANTILE CEREBRAL PALSY CITY OF SEVERSK - A. V. Rogov; E. F. Levickii; R. Z. Barabash; S. D. Korshunov; T. G. Dorosheva; Ye. I. Nechayeva; V. K. Pashkov (Медицинский вестник Юга России, 2014)
Purpose: To evaluate the catamnesis of 120 patients with spastic form of cerebral palsy.Materials and methods: It was studied obstetric-gynecological anamnesis and rehabilitation of 120 patients with spastic form of cerebral  palsy of the closed administrative territorial entity Seversk.Results: The risk factors of patients with cerebral palsy in Seversk did not differ in comparison with the average data for the Russian Federation.Summary: The main cause of disability among the examined patients with cerebral palsy of Seversk city was an extremly low and very low body weight, combined with the evaluation on  Apgar scale 4-5 points and below.